Pengaruh Citra Destinasi Dan Kualitas Pelayanan Terhadap Minat Kunjungan Kembali Wisatawan (Studi Pada Destinasi Wisata Air Panas Padusan Kecamatan Pacet Mojokerto) - Akhmad Farikhin; Muhammad Mansur; Achmad Agus Priyono (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstrackThis study is entitled "The Effect of Destination Imagery and Service Quality on Interest in Tourist Returns (Study on Padusan Hot Spring Tourism)". This study raises the issue of how the Influence of Destination Imagery and Service Quality on Tourist Return Interests. The purpose of this study was to determine how the Influence of Destination Imagery and Service Quality on Tourist Return Interests The analytical tool used is Quantitative Descriptive regression analysis with Multiple Linear Regression analysis. The results of the analysis can be found that there is a significant positive effect on the Destination Image and Service Quality on the Tourist Visit Interests. Based on the results of the research, the implication of this study is the need for an increase in destination image and service quality in order to increase the interest of tourist return visits in accordance with the empirical results of this study which state that destination image and service quality can increase tourist return visit interest. Keywords: Destination Goals, Service Quality and Interest of Tourist Return Visit.